Growth Pattern and Copper Accumulation in Callus of Datura metel - Yulita Nurchayati; Santosa Santosa; Laurentius Hartanto Nugroho; Ari Indrianto (Biosaintifika: Journal of Biology & Biology Education)
This experiment was aimed to evaluate the copper accumulation using callus culture of Datura metel L. The culture was established from leaves onto MS contained NAA 2.5 mg/L and Kinetin 0.5 mg/L as the control. The exposure of the culture was carried out by 2 copper compounds as treatment, i.e. CuCl2.2H2O and Na2CuEDTA at level concentration 0.; 0.1; 5; 10; 15; and 20 µM. The growth pattern of callus in control showed increasing growth rate in 36 days, whereas exponential stage was reached at 12-20th doi*. Whilst, after 10 doi, the treatment showed constant growth pattern. The absorption rate of the culture was increased by the addition of the CuCl2.2H2O at 5 – 15 µM of level concentration but declined at 20µM. The maximum rate of accumulation of Cu (0,1519 mg g-1) was obtained at 15 µM. Instead, the addition of Na2CuEDTA at 5 – 20µM of level concentration showed the significant increment while the maximum accumulation was obtained at 20µM (0,1420 mg g-1). The existence of chelator in copper compound reduced the rate of toxicity while all tolerance index values were between 66,24 and 97,28 %.The results suggested the role of callus of D. metel as  that fairly absorbed and accumulated Cu2+. Exposure with CuCl2.2H2O indicated higher accumulation than Na2CuEDTA. How to Cite Nurchayati, Y., Santosa, S., Nugroho, L. H., & Indrianto, A. (2016). Growth Pattern and Copper Accumulation in Callus of Datura metel. Biosaintifika: Journal of Biology & Biology Education, 8(2), 135-140.